Use of Phyto-Additives in Poultry Nutrition - Teodor Gavris; Untea Arabela; Mihaela Saracila (Scientific Papers Animal Science and Biotechnologies, 2023)
This article presents experimental data on the properties, efficacy and modes of action of phyto-additives that can be used in poultry nutrition. Phyto-additives are a great variety of herbs, spices and products derived from them, as well as essential oils.  The content of active substances in these products can vary greatly depending on what part of the plant is used (grains, leaves, roots, bark, flowers, or buds), the harvest season and geographical origin and technique of treatment (cold, steam distillation, extraction or maceration with non-aqueous solvents, etc.). The uses of phyto-additives are still limited in relation to their mode of action and aspects of application in poultry nutrition. Phyto-additives are supposed to improve the palatability of feed and hence improve performance. Although many studies have demonstrated antioxidant and antimicrobial efficacy in vitro, this still remains to be checked in vivo. It is also assumed that phyto-additives improve nutrient absorption and enzymatic activity of poultry digestive tract. However, the limited number of comparative studies between phyto-additives and antibiotics suggests that they can have beneficial effects on the digestive tract by reducing the number of implicit bacteria and metabolites produced by them. Other studies show that phyto-additive use in animal feed improves the secretion of intestinal mucus. Also, a systematic approach to the effectiveness, dose, mode of action and safety of phyto-additives in poultry feed is not yet well established.